Energy forecasts: some issues - Scott, S. (Statistical and Social Inquiry Society of Ireland, 1979)
A realistic set of energy forecasts is fundamental to the formulation of energy policy, yet it would be hard for forecasters in this field to feel anything but massive uncertainty about their projections. In the foreword to the Department's Energy Forecasts 1978-1990 is stated: "the enclosed forecasts will need to be reviewed from time to time in the light of new information and changing circumstances". These changing circumstances relate not only to GDP, population, indigenous energy supplies and energy price, but also to changing technology and social behaviour. Many forecasters feel that they are on shifting ground and at the moment this is particularly true of the energy forecaster. It would, therefore, be a step in the right direction if we can simply get a feel for some orders of magnitude and establish the existence or otherwise of some important relationships. This papers starts with a brief analysis of the official forecasts for 1990 and finds some indications that these are on the high side. There follows a report on some independent time-series studies which yield projections ranging below the official best estimate and, perhaps more important, throw some light on the responsiveness of energy demand to price.
Symposium on Future Demands for and Supplies of Energy
Read before the Society, 5 April 1979
Keywords: Energy supply; Energy demand; Forecasting engergy supply and demand; 314.15